GIANT MALT-LYMPHOMA WITH MENETRIER’S DISEASE COMPLICATED BY STENOSIS AND OBSTRUCTION OF THE STOMACH - U. S. Beslekoev; Ts. S. Khutiev; S. Ts. Khutiev; М. Т. Zaseeva (Сибирский онкологический журнал, 2016)
A rare case of successful surgical treatment of giant MALT-lymphoma with Menetrier’s disease complicated by gastric obstruction has been presented.